2017
DOI: 10.18632/oncotarget.20089
|View full text |Cite
|
Sign up to set email alerts
|

CD147 expression was positively linked to aggressiveness and worse prognosis of gastric cancer: a meta and bioinformatics analysis

Abstract: CD147 (also named as Basigin or EMMPRIN) might promote cancer invasion and metastasis by inducing MMP and VEGF synthesis in tumor microenvironment. We performed a systematic meta and bioinformatics analysis through multiple online databases up to March 14, 2017. Up-regulated CD147 expression was found in gastric cancer, compared with normal mucosa (p < 0.05). The male patients with gastric cancer showed higher CD147 expression than the female ones (p < 0.0001). CD147 expression was positively correlated with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
3
6
0
Order By: Relevance
“…Moreover, some scholars detected a high expression of CD 147 in gastric cancer. In a meta and bioinformatics analysis, Zheng and colleagues7 found that the expression of CD147 was positively correlated with tumor size, depth of invasion, lymph node metastasis, TNM staging and unfavorable prognosis in gastric cancer 7. We had the same conclusion in this study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, some scholars detected a high expression of CD 147 in gastric cancer. In a meta and bioinformatics analysis, Zheng and colleagues7 found that the expression of CD147 was positively correlated with tumor size, depth of invasion, lymph node metastasis, TNM staging and unfavorable prognosis in gastric cancer 7. We had the same conclusion in this study.…”
Section: Discussionsupporting
confidence: 76%
“…In addition, CD147 and miR203 were also studied by scholars as their close relationship with gastric cancer. CD147, which was isolated from lung carcinoma cells, can increase cancer invasion by inducing MMP synthesis in neighboring fibroblasts, endothelial and cancer cells 7. Chu investigated the level of CD147 in 223 gastric cancer patients, and confirmed the association of CD147 with gastric cancer invasion and metastasis, suggesting that CD147 may be an indicator of tumor recurrence and prognosis 8.…”
Section: Introductionmentioning
confidence: 86%
“…CD147, also termed as EMMPRIN or basigin, is a pleiotropic molecule with various effects (Grass & Toole, 2016 ; Iacono et al., 2007 ). Given the emerging use of bioinformatics in biological research (Karim et al., 2020 ; Mehmood et al., 2014 ), it is worth mentioning that, through pathway analyses, CD147 was found to be a significant cell-surface protein contributing to chemoresistance and cell survival in cancer-stem-cell-like cells (Kang et al., 2013 ), and the invasion of various cancers (Li et al., 2015 ; Liang et al., 2016 ; Zheng & Gong, 2017 ). Additionally, it was found to be highly expressed in activated regulatory T lymphocytes, enabling it to be a potential marker for distinguishing cytokine-producing activated T lymphocytes from resting T lymphocytes (Landskron & Taskén, 2013 ; Solstad et al., 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…CD147, a transmembrane glycoprotein, belongs to the immunoglobulin superfamily and is widely expressed on the surface of cancer cells . Reports showed that CD147 was over‐expressed in many types of cancer, such as human malignant melanoma, hepatocellular carcinoma, lung cancer, gastric cancer, breast cancer and so on . CD147 is also reported to involve in tumor progression, angiogenic function and immune response …”
Section: Introductionmentioning
confidence: 99%
“…6 Reports showed that CD147 was over-expressed in many types of cancer, such as human malignant melanoma, hepatocellular carcinoma, lung cancer, gastric cancer, breast cancer and so on. [7][8][9][10][11][12] CD147 is also reported to involve in tumor progression, angiogenic function and immune response. 13,14 Furthermore, many studies demonstrated that CD147 could stimulate the activation of nuclear factor kappa B (NF-kappa B) pathway.…”
mentioning
confidence: 99%